Vibration analysis on a composite beam and damage identification using finite element analysis - Ramanamurthy, E.V.V.; Chandrasekaran, K. (Journal of Structural Engineering, 2024)
Vibration based damage identification has gained a lot of importance in recent years with increasing applications of composite structures in many areas of engineering. Since the modal parameters are related to the physical properties of the laminates, changes could be easily detected when damage occurs in these structures. A number of analytical, numerical and experimental techniques are available for the study of damage identification in beams. The objective of this paper is to develop a damage detection method in a composite cantilever beam with an edge crack which has been studied using finite element method. The task is then to monitor the selected indicators derived from modal parameters to distinguish between undamaged and damaged states. There have been several studies dealing with the detection of damage through analysis of some of the commonly measured modal parameters, especially the frequencies and mode shapes. However, not many of them deal with laminated composites. An alternative to using mode shapes is to obtainspatial information about vibration changes, using mode shape derivatives, such as curvature. The curvature can be obtained by calculation from displacement modal shapes or measuring the curvatures/strain directly. By using a cantilever beam model, it is demonstrated that the absolute changes in modeshape curvature are localised in the region of damage and hence can be a good indicator of damage in the structure. Finite element analysis is used to obtain the displacement mode shapes of a cantilever beam model. The curvature values are computed from the displacement mode shapes using a central difference approximation. The validity of the analysis is established through comparisons with available published literature. In this study, damage identification is based on the damage index method. The importance of using damage patterns from the damage index method, (which is based on changes in modal strain energies) is that only measured mode shapes are required in the damage identification. The results show, the damage index based method is capable of identification of damage and severity of damage in a structure.